USER-GENERATED-CONTENT MARKETING STRATEGIES IN PROVISION OF CONSUMER RESPONSIBILITY - Varadainy, Zilba; Helita , Widia; Hermansyah, Mamad; Rahmawati, Imelda Dian (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study examines the effectiveness of a user-generated content (UGC) marketing strategy in increasing consumer engagement. The research findings indicate that UGC marketing strategies can significantly enhance consumer engagement and strengthen the trust relationship between consumers and the brand. Audiences tend to trust consumer-generated content more than traditional marketing content due to its authenticity and genuineness. Therefore, marketers are advised to leverage UGC as one of the most effective marketing strategies to increase consumer involvement and achieve marketing objectives. By integrating UGC into their marketing strategies, brands can create closer relationships with their consumers and strengthen their market position.